Fracture Resistance of a Bulk-Fill and a Conventional Composite and a Combination of both for Coronal Restoration of Severely Damaged Primary Anterior Teeth - Shahram Mosharrafian; Maryam Shafizadeh; Zeinab Sharifi (Tehran University of Medical Sciences, 2019)
Objectives: This study aimed to compare the fracture resistance of a bulk-fill and a conventional composite and a combination of both for coronal restoration of severely damaged primary anterior teeth. Materials and Methods: In this in vitro experimental study, 45 primary anterior teeth were randomly divided into three groups. After root canal preparation, the canals were filled with Metapex paste such that after the application of 1 mm of light-cure liner, 3 mm of the coronal third of the canal remained empty for composite post fabrication. Filtek Z250 conventional composite was used in group 1, Sonic-Fill bulk-fill composite was used in group 2 and Sonic-Fill with one layer of Filtek Z250 as the veneering were used in group 3. Adper Single Bond 2 was used in all groups. The teeth were thermocycled, and fracture resistance was measured by a universal testing machine. The mode of fracture was categorized as repairable or irreparable. Data were analyzed using one-way ANOVA. Results: The mean fracture resistance was 307.00±74.72, 323.31±84.28 and 333.30±63.96 N in groups 1 to 3, respectively (P=0.55). The mean fracture strength was 14.53±2.98, 15.08±2.82 and 15.26±3.02 MPa in groups 1 to 3, respectively (P=0.77). The frequency of repairable mode of failure was 80% for the conventional, 73.6% for the bulk-fill and 80% for the bulk-fill plus conventional group, with no significant difference (P>0.05). Conclusions: Bulk-fill composites can be used for coronal reconstruction of severely damaged primary anterior teeth similar to conventional composites to decrease the treatment time in pediatric patients.